Neil patrick harris ebook Choose your own autobiography. - Harris, Neil Patrick (2014)
NEW YORK TIMES BESTSELLER • Tired of memoirs that only tell you what really happened? Sick of deeply personal accounts written in the first person? Seeking an exciting, interactive read that puts the “u” back in “aUtobiography”? Then look no further than Neil Patrick Harris: Choose Your Own Autobiography ! In this revolutionary, Joycean experiment in light celebrity narrative, actor/personality/carbon-based-life-form Neil Patrick Harris lets you, the reader, live his life. You will be born to New Mexico. You will get your big break at an acting camp. You will get into a bizarre confrontation outside a nightclub with actor Scott Caan. Even better, at each critical juncture of your life you will choose how to proceed. You will decide whether to try out for Doogie Howser, M.D. You will decide whether to spend years struggling with your sexuality. You will decide what kind of caviar you want to eat on board Elton John’s yacht. Choose correctly and you’ll find fame, fortune, and true love. Choose incorrectly and you’ll find misery, heartbreak, and a hideous death by piranhas. All this, plus magic tricks, cocktail recipes, embarrassing pictures from your time as a child actor, and even a closing song. Yes, if you buy one book this year, congratulations on being above the American average, and make that book Neil Patrick Harris: Choose Your Own Autobiography ! “Neil Patrick Harris’s Choose Your Own Autobiography is one of the best celeb memoirs I’ve ever read.”— Phoenix News